265 Evaluation of the genetic relationship amongst high elevation pulmonary arterial pressure, feedlot and carcass performance traits. (30th November 2020) - Briggs, Emma A; Speidel, Scott; Enns, Mark; Thomas, Milt; Holt, Tim
Abstract: The objective of the study was to evaluate if a genetic relationship exists between pulmonary arterial pressure (PAP) measured at high elevation with traits associated with moderate elevation feedlot and carcass traits. For this analysis, PAP, feed intake, and carcass data were taken from 6, 898, 558, and 1, 627 animals, respectively. At an elevation of 2, 115 m, PAP measurements were collected, then a selective group of steers was relocated to a moderate elevation feedlot (1, 500 m) where feed intake data were collected. Genetic relationships were evaluated with 5-trait animal models using REML statistical analysis. For all traits in the analysis, fixed effects and contemporary groups were assigned as well as a direct genetic random effect. For weaning weight, a maternal permanent environmental effect was applied in the analysis. For PAP, the heritability estimate was 0.29 ± 0.03. Genetic correlations between PAP with feedlot traits was positive, with estimates of 0.34 ± 0.20 (average dry matter intake) and 0.05 ± 17 (average daily gain). The strongest genetic correlation between PAP and carcass performance traits were those of rib eye area (-0.30 ± 0.12) and calculated yield grade (0.29 ± 0.13). Genetic correlations between PAP and marbling score, back fat, or hot carcass weight were 0.00 ± 0.13, -0.07 ± 0.13, and 0.14 ± 0.10, respectively. These results suggest a favorable genetic relationship exists between PAP with feedlot and carcass traits.